(untitled) (Intent Research Scientific Journal, 2025)
This article analyzes modern measures aimed at preventing accidents and disasters that may occur during the drilling of oil and gas wells. The causes of dangerous situations during drilling operations, methods for their elimination, as well as advanced technologies for ensuring safety are considered. The information is enriched with recommendations for practical application.